2017
DOI: 10.1590/01047760201723042414
|View full text |Cite
|
Sign up to set email alerts
|

GENERAL HEIGHT-DIAMETER EQUATION WITH BIOLOGICAL ATTRIBUTES FOR Pinus taeda L. STANDS

Abstract: The aim of this study was to develop an equation with biological attributes and general applicability, to represent the height-diameter relationship for Pinus taeda L. stands, with and without thinning, in the Middle West region of Santa Catarina state, Brazil. The data came from 652 permanent plots, with 428 to 740 m2, located in forest stands with ages ranging from 4.6 to 35.2 years, in which the total heights of about 20% of the trees were measured, in addition to the dominant trees. The functions developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Similar to the results found in this study, Téo et al (2017) reported the best statistical performance for Harrison et al (1986) model adjusted with its parameters expressed as a linear function of stand variables, to represent the heightdiameter relationship of Pinus taeda L. in the Midwest region of Santa Catarina State, Brazil. The different versions of the Harrison et al (1986) model, adjusted by Téo et al (2017), also presented negative bias (MD).…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Similar to the results found in this study, Téo et al (2017) reported the best statistical performance for Harrison et al (1986) model adjusted with its parameters expressed as a linear function of stand variables, to represent the heightdiameter relationship of Pinus taeda L. in the Midwest region of Santa Catarina State, Brazil. The different versions of the Harrison et al (1986) model, adjusted by Téo et al (2017), also presented negative bias (MD).…”
Section: Resultssupporting
confidence: 84%
“…The Harrison et al (1986) model adjusted with its parameters expressed as a linear function of stand variables, by ordinary least squares, produced distribution of studentized residuals without heteroscedasticity and without evidences of non-normality, then weighted least squares regression with Parresol (1993) and Huber (1964) methods were not necessary (Figure 2). Téo et al (2017) reported studentized residuals without heteroscedasticity, but with evidences of non-normality of the residuals, especially with large residuals at both extremes of the distribution of errors for the Harrison et al (1986) 3). Among the different versions of the Harrison et al (1986) 3,1978 -3,33 7,19 Where: EM = modeling efficiency; MAD PRESS = average of the PRESS differences; MAD PRESS = average of the PRESS absolute differences; P5 = 5% percentile value of the PRESS residuals; P95 = 95% percentile value of the PRESS residuals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations